Risk Factors for Atorvastatin as a Monotherapy for Chronic Subdural Hematoma: A Retrospective Multifactor Analysis - Zhang, Xinjie; Wang, Dong; Tian, Ye; Wei, Huijie; Liu, Xuanhui; Xiang, Tangtang; Fan, Yibing; Gao, Chuang; Huang, Jinhao; Sha, Zhuang; Quan, Wei; Zhang, Jianning; et al. (Frontiers in Aging Neuroscience, 2021)
Chronic subdural hematoma (CSDH) is a common form of intracranial hemorrhage in the aging population. We aimed to investigate the predictive factors for atorvastatin efficacy as a monotherapy for moderate CSDH.We retrospectively reviewed the medical records of patients who were diagnosed with moderate CSDH and received atorvastatin monotherapy between February 5, 2014, and November 7, 2015, in multiple neurosurgical departments. Univariate, multivariate and receiver operating characteristic curve analyses were performed to identify the potential significant factors indicative of the good therapeutic efficacy or poor therapeutic efficacy of atorvastatin for mild CSDH, such as age, sex, history of injury, Markwalder grading scale–Glasgow Coma Scale （MGS-GCS）, activities of daily living–Barthel Index (ADL-BI), American Society of Anesthesiologists Physical Status classification system (ASA-PS), blood cell counts, serum levels and computed tomography findings.A total of 89 patients (75 men and 14 women) aged 24-88 years (mean age 61.95±15.30 years) were followed-up for 24 weeks. Computed tomography findings at admission showed mixed-density hematoma in 22 patients, isodense hematoma in 13 patients, high-density hematoma in 26 patients, and low-density hematoma in 28 patients. In total, 3, 80, and 6 patients had MGS-GCS grades of 0, 1, and 2, respectively. The efficacy rate at 6 months was 87.6% (78/89). Eleven patients were switched to surgery due to a worsened neurological condition, of whom 8, 1, 1, and 1 had high-density, low-density, isodenseand mixed-density hematomas, respectively. These patients were switched to surgery over a range of 2-27 days, with a median interval of 12 days after the medication treatment. Univariate and multivariate analyses, confirmed by ROC curves, revealed that high-density hematoma, basal cistern compression, and hematoma volume to be independent risk factors for the efficacy of atorvastatin monotherapy in patients with moderate CSDH. Atorvastatin is an effective monotherapy for the treatment of mild CSDH. High-density hematoma, basal cistern compression, and hematoma volume are independent predictors of the efficacy of atorvastatin as a nonsurgical treatment. The results suggested that ADL-BI was more sensitive than the MGS-GCS and ASA-PS for determining patient outcomes in our moderate CSDH cohort.